Adolescents' Perceptions of Suicide (Research, Society and Development, 2021)
The study aims to understand the perception of adolescents about suicide in a high school in Sobral-Ceará, Brazil. Descriptive exploratory study with a qualitative approach conducted with 30 teenagers, from the 3rd year of high school at a school in the interior of Ceará, in September 2018. The research used a semi-structured interview with the following questions: What do you understand by suicide? Can you identify a suicidal idea? If yes, describe. If you knew someone who would be thinking about committing suicide what would you do to try to help them? The analysis of the information followed the precepts of Minayo (2010). It was evident that adolescents have knowledge on the subject, as well as some support strategies in the face of suicide. Most adolescents reported that their first contact with the topic of suicide was at school, and that they knew or lived with someone who had already committed suicide with it. It is noteworthy that this work can encourage both family members and in the field of care to guide adolescents about suicide and about breaking the taboo that this topic has. It also reinforces the importance of conducting further research on the subject, to expand new intervention strategies with this group and the health and education institutions involved.